Rodzic w pracy. Organizacja pracy na uczelni wyższej w kontekście rodzicielstwa - Achremowicz, Hanna; Chmiel, Anna; Kamińska-Sztark, Kamila; Pilawska-Gronostaj, Roksana; Pryszmont, Martyna; Wylęgły, Kamila (Wydawnictwo Naukowe EDUsfera, 2022)
The aim of the article is to present the results of research on the organization of work during the COVID-19 pandemic among scientific, administrative, and technical employees of the University of Wrocław and the possibility of childcare for people working at the University of Wrocław in scientific, and non-scientific, positions.
Keywords: working conditions; gender equality; university; higher education institution